DNA damage, demethylation and anticancer activity of DNA methyltransferase (DNMT) inhibitors - Angelo B. A. Laranjeira; Melinda G. Hollingshead; Dat Nguyen; Robert J. Kinders; James H. Doroshow; Sherry X. Yang (Scientific Reports, 2023)
Abstract Role of DNA damage and demethylation on anticancer activity of DNA methyltransferase inhibitors (DNMTi) remains undefined. We report the effects of DNMT1 gene deletion/disruption (DNMT1 −/− ) on anticancer activity of a class of DNMTi in vitro, in vivo and in human cancers. The gene deletion markedly attenuated cytotoxicity and growth inhibition mediated by decitabine, azacitidine and 5-aza-4′-thio-2′-deoxycytidine (aza-T-dCyd) in colon and breast cancer cells. The drugs induced DNA damage that concurred with DNMT1 inhibition, subsequent G2/M cell-cycle arrest and apoptosis, and upregulated p21 in DNMT1 +/+ versus DNMT1 −/− status, with aza-T-dCyd the most potent. Tumor growth and DNMT1 were significantly inhibited, and p21 was upmodulated in mice bearing HCT116 DNMT1+/+ xenograft and bladder PDX tumors. DNMT1 gene deletion occurred in ~ 9% human colon cancers and other cancer types at varying degrees. Decitabine and azacitidine demethylated CDKN2A/CDKN2B genes in DNMT1 +/+ and DNMT1 −/− conditions and increased histone-H3 acetylation with re-expression of p16INK4A/p15INK4B in DNMT1 −/− state. Thus, DNMT1 deletion confers resistance to DNMTi, and their anti-cancer activity is determined by DNA damage effects. Patients with DNMT1 gene deletions may not respond to DNMTi treatment.